2020
DOI: 10.1111/jfbc.13140
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diets and protective mechanisms in epilepsy, metabolic disorders, cancer, neuronal loss, and muscle and nerve degeneration

Abstract: Ketogenic diet (KD), the “High‐fat, low‐carbohydrate, adequate‐protein” diet strategy, replacing glucose with ketone bodies, is effective against several diseases, from intractable epileptic seizures, metabolic disorders, tumors, autosomal dominant polycystic kidney disease, and neurodegeneration to skeletal muscle atrophy and peripheral neuropathy. Key mechanisms include augmented mitochondrial efficiency, reduced oxidative stress, and regulated phospho‐AMP‐activated protein kinase, gamma‐aminobutyric acid‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 108 publications
0
65
0
3
Order By: Relevance
“…The ketogenic diet has been widely used in the treatment of a variety of neurological and metabolicrelated diseases, especially epilepsy [22][23]. In recent years, some studies, including previous studies performed by our team, have shown that the ketogenic diet has a protective effect after spinal cord injury by increasing the spontaneous movement and ne manipulation of SCI animal models [17,[24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet has been widely used in the treatment of a variety of neurological and metabolicrelated diseases, especially epilepsy [22][23]. In recent years, some studies, including previous studies performed by our team, have shown that the ketogenic diet has a protective effect after spinal cord injury by increasing the spontaneous movement and ne manipulation of SCI animal models [17,[24][25].…”
Section: Discussionmentioning
confidence: 99%
“…been successfully applied in conditions that include epilepsy, metabolic disorders, cancer, neuronal loss, and muscle and nerve degeneration (46,47). The diets have also been successful in reducing excess body fat (48) and chronic inflammation (49).…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%
“…Ketogena dijeta je niskougljenohidratna ishrana, sa visokom unosom masti i adekvatnom unosom proteina (1 g/kg TM). U nedostatku ugljenih hidrata (UH) organizam je primoran da koristi masti kao izvor energije koje prvo pretvara u ketone, koji će kod ove vrste dijete biti prisutni u povećanim količinama u krvi i urinu (49). Ključni mehanizam delovanja KD na mozak, neuronsku funkciju i oslobađanje neurotransmitera uključuje povecánu efikasnost mitohondrija, regulaciju AMP-aktivirane protein kinaze, Na+/K+ pumpe, leptina, glutaminske kiseline, lipogenezu, ketogenezu, lipolizu i glukoneogenezu.…”
Section: Ketogena Dijetaunclassified
“…KD ima potencijalno antioksidativno i protivupalno dejstvo preko smanjenja oksidativnog stresa i dovodi do stabilizacije nivoa glukoze. Zatim, podstiče perifernu aksonsku i senzornu regeneraciju, ketonska tela i masne kiseline imaju potencijalni antiepileptični efekat (49,50).…”
Section: Ketogena Dijetaunclassified